Arrhythmogenic risk of pulmonary artery catheterisation in patients with severe aortic stenosis undergoing transcatheter aortic valve implantation. (5th November 2012) - Bergmann, L.; Großwendt, T.; Kahlert, P.; Konorza, T.; Wendt, D.; Thielmann, M.; Heusch, G.; Peters, J.; Kottenberg, E.
Summary Many clinicians consider severe aortic stenosis to be a contraindication to pulmonary artery catheterisation, except during open heart surgery with cardiopulmonary bypass. This is due to the perceived high risk of arrhythmia, although the true incidence of ventricular tachycardia and fibrillation remains unclear. We conducted a retrospective study to estimate the incidence of severe arrhythmias during pulmonary artery catheterisation in 380 patients with severe aortic stenosis scheduled for transcatheter aortic valve implantation. Ventricular fibrillation was seen in only one patient (0.26%), and this was successfully terminated by external defibrillation. No episodes of ventricular tachycardia were recorded and there were also no arrhythmias during removal of the catheter. We have therefore concluded that pulmonary artery catheterisation in patients with severe aortic stenosis is not associated with a high incidence of ventricular fibrillation or tachycardia, allowing pulmonary artery pressure monitoring to be performed relatively safely in such patients.